Introduction to optimization and semidifferential calculus - Delfour, Michel C. 1943- (Society for Industrial and Applied Mathematics (SIAM), 2012)
This primarily undergraduate textbook focuses on finite-dimensional optimization. Readers will find: an original and well integrated treatment of semidifferential calculus and optimization; emphasis on the Hadamard subdifferential, introduced at the beginning of the 20th century and somewhat overlooked for many years, with references to original papers by Hadamard (1923) and Fr echet (1925); fundamentals of convex analysis (convexification, Fenchel duality, linear and quadratic programming, two-person zero-sum games, Lagrange primal and dual problems, semiconvex and semiconcave functions); complete definitions, theorems, and detailed proofs, even though it is not necessary to work through all of them; commentaries that put the subject into historical perspective; numerous examples and exercises throughout each chapter, and answers to the exercises provided in an appendix
Keywords: Mathematical optimization; Differential calculus; Variationsrechnung; Lehrbuch